Kernohan's notch phenomenon demonstrated by diffusion tensor imaging and transcranial magnetic stimulation. Issue 11 (21st October 2008) - Yoo, W-K; Kim, D-S; Kwon, Y H; Jang, S H
Abstract : Kernohan's notch phenomenon is the ipsilateral hemiplegia caused by compression of the contralateral cerebral peduncle against the tentorial edge by a supratentorial mass. Diffusion tensor imaging (DTI) and transcranial magnetic stimulation (TMS) could be useful for exploring the state of the corticospinal tract (CST). This report attempts to demonstrate Kernohan's notch phenomenon in a patient with subdural haematoma by using DTI and TMS. One patient and six normal control subjects were recruited. The patient showed severe right hemiplegia even though the subdural haematoma was located in the right hemisphere. Brain CT at the time of onset showed right transtentorial herniation, and T2 weighted images at 6 weeks after onset showed a leucomalacic lesion on the left cerebral peduncle. DTI and TMS were performed at 6 weeks after onset. The fractional anisotrophy value of the left midbrain and medulla of the patient was found to be decreased in comparison with that of the control subjects. On fibre tractography for the CST, an interruption was observed in the left midbrain and medulla. The motor evoked potential obtained from the right hand muscle showed delayed latency, low amplitude and a higher excitatory threshold, thus indicating that the CST of the left hemisphere had been damaged. It seems that the CST had been damaged at the left midbrain, although subdural haematoma and transtentorial herniation had occurred in the right hemisphere in this patient. This report demonstrates Kernohan's notch phenomenon in this patient using DTI and TMS.